Medical assistance in dying: Examining Canadian pharmacy perspectives using a mixed-methods approach. (March 2018) - Verweel, Lee; Rosenberg-Yunger, Zahava R. S.; Movahedi, Taranom; Malek, Allan H.
Background: Canada legalized assisted dying with the passing of Bill C-14, Medical Assistance in Dying (MAiD), in June 2016. This legislation has implications for health care professionals participating in MAiD. This research aims to understand the effect that MAiD has on pharmacists and pharmacy technicians in Canada. Methods: We conducted a thematic document analysis of pharmacy guidelines, position statements and standards of practice from pharmacy regulatory authorities across Canada. In addition, the Ontario Pharmacists Association surveyed its members (including pharmacists, pharmacy technicians and pharmacy students) about their perceptions of MAiD. Results: Our thematic analysis of the reviewed documents resulted in 3 major themes: pharmacists' role in quality assurance, practice considerations when implementing MAiD and resources for pharmacy staff involved in MAiD. Survey responses illustrated that most (68%) pharmacy staff would dispense MAiD medications. Nonetheless, many respondents perceived that they lacked knowledge or comfort with different aspects of the MAiD process. Overall, 80% of participants reported a desire for professional development about MAiD. Conclusion: Despite the rapidly changing landscape surrounding medical assistance in dying within the past year, most pharmacy regulatory authorities have provided direction and resources to their pharmacists. Ontario pharmacists and pharmacy technicians are willing to dispense MAiD medications; however, additional support in the form of professional development may be necessary based on participants' desire for education coupled with their perceived lack of knowledge. Future research may focus on the efficacy of provincial guidelines in supporting pharmacists' participation in MAiD.